Frequency domain electromagnetic and electrical resistivity geophysical investigation of tar sands deposits in the Ijebu Waterside area, Eastern Dahomey Basin, southwestern Nigeria - Osinowo, Olawale Olakunle; Okechukwu, Ifeayinchukwu (Geology, Geophysics and Environment, 2021)
The use of electromagnetic conductivity and electrical resistivity geophysical techniques has been employed in this study to investigate the occurrence, thickness, and spatial distribution of bitumen deposit around Makun-Omi in the Ijebu Waterside area of southwestern Nigeria. Subsurface apparent conductivity distribution data obtained using Geonic 34-3 equipment along fifteen traverses which sounded from different depths of 7.5, 15, 30 and 60 m at inter-coil separation of 10, 20 and 40 m in vertical and horizontal coupling modes and ground resistivity distribution measurements, obtained using Geopulse Tiger Allied resistivity meter at fourteen Vertical Electrical Sounding (VES) stations, were processed and employed to characterize the subsurface in terms of tar sands distribution. The conductivity and resistivity distribution in the form of a 3D earth model, iso-depth maps, 2D sections generated from the processed conductivity and resistivity data indicate relatively low conductivity <20 mS/m and high resistivity >1300 Ωm values around tar/bitumen impregnated sands which mostly occurred in the southern part of the study area. Clearly defined conductivity and resistivity anomalies which delineate the lateral and vertical occurrence of tar impregnated sands underscore the efficacy of integrating electromagnetic and electrical resistivity geophysical techniques to identify occurrence of economic deposits of tar sands in parts of southwestern Nigeria.